Rapid response to emerging biomedical challenges and threats. (2021) - Grabowski, Marek; Macnar, Joanna M.; Cymborowski, Marcin; Cooper, David R.; Shabalin, Ivan G.; Gilski, Miroslaw; Brzezinski, Dariusz; Kowiel, Marcin; Dauter, Zbigniew; Rupp, Bernhard; Wlodawer, Alexander; Jaskolskid, Mariusz; et al.
No abstract available